RATIONALITY OF MODERN PHILOSOPHICAL DISCOURSE - E. Sergodeeva (Гуманитарные и юридические исследования)
The paper analyzes the changes of philosophical discourse which are typical of contemporary intellectual situation and viewed through the lens of transformation of scientific rationality and intellectual practices in general. It is noted that in contemporary culture the field of rationality has been expanding and there has been a steady trend of changing the format of philosophical discourse in the direction of literature and literary criticism. The author proves the idea that the modern philosophical discourse is characterized by fundamental differences in comparison with the classical standards of philosophical rationality.